Co-composting cow manure with food waste: The influence of lipids content - Neves, L. (2009)
Addition of an oily waste to a co-composting process of dairy cow manure with food waste, and the influence in the final product was evaluated. Three static composting piles with different substrates concentrations were assessed. Sawdust was also added to all composting piles to attain 60%, humidity at the beginning of the process. In pile 1, the co-substrates were the solid-phase of dairy cow manure, food waste and sawdust as bulking agent. In piles 2 and 3 there was an extra input of oily waste of 7 and 11% of the total volume, respectively, corresponding to 18 and 28% in dry weight. The results showed that the co-composting process was feasible even at the highest fat content. Another positive effect due to the oily waste addition was the requirement of extra humidity, due to the hydrophobic properties of this specific waste, which may imply reduced need of a bulking agent. Moreover, this study shows that composting can be a feasible way of adding value to fatty wastes. The three final composts presented very similar and suitable properties for land application.